Optimized scratch adhesion for TiSiN coatings deposited by a combination of DC and RF sputtering - Bushroa, Abdul Razak; Masjuki, Haji Hassan; Muhamad, Muhamad Rasat; Beake, B.D. (Elsevier, 2011)
This paper outlines an experimental study of the TiSiN coatings deposited using a combination of direct current (DC) and radio frequency (RF) PVD magnetron sputtering (DR-PVD) on high speed steel (HSS) substrates. An L9 Taguchi orthogonal array was used to conduct the experiments for finding the optimum process parameters. Four process parameters, (1) RF power, (2) DC power, (3) nitrogen to argon (N2/Ar) gas ratio and (4) deposition time were considered. The surface structure and composition of selected coating samples were studied by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The critical load in the micro-scratch test was used as a measure of scratch adhesion. Investigations of the scratch tracks were viewed by an optical microscope. The results showed that higher scratch adhesion strength was achieved using RF power of 100 W, DC power of 500 W, N2/Ar ratio of 1:2.5 and a deposition time of 6 h. Optimization resulted in an increase of the critical load value from 827 mN to 1371 mN, signifying an improvement of over 65%.